Factors Influencing the Success of Corporate Merger in Malaysia: The Case of Rothmans Pall Mall (Malaysia) Limited and Malaysian Tobacco Company Limited (MTC) - Syed Hussain, Syed Husman (2022)
Rothmans of Pall Mall (Malaysia) Berhad was incorporated in the Federation of Malaya on 11 September 1961 with an authorised capital of RM20,000,000. The Company was the first Rothmans venture in Asia and became the first overseas tobacco company to offer 50% of its holdings to the Malaysian public. On 31 October 1985, the company announced proposals for a restructuring of its equity in line with the Malaysia's National Economic Policy (NEP). Revised in May 1986, the scheme increased the Bumiputera shareholding in the Company from 4% to 30% without departing from the equity partnership, whereby the company was 50% owned by Rothmans International plc and 50% by local investors. Malaysian Tobacco Company Berhad (MTC) was incorporated in the Federation of Malaya on 28 September 1956 as Malayan Tobacco Company. It was converted into a public company in February 1962. The company's name was changed to Malaysian Tobacco Company Berhad on 17 March 1977. The company was formed to take over the business of Malayan Tobacco Distributors Ltd (MTDL), a subsidiary of British-American Tobacco Co Ltd. In 1979, MTC started a modernisation programme (completed in 1987) which has provided up-to-date manufacturing and processing facilities at both its Sungai Besi and Shah Alam factories. Given this background, the scope of this research are between two synergic companies; Malaysian Tobacco Company Berhad (MTC) and Pall Malls (Malaysia) Limited as British American Tobacco (Malaysia) Limited – BAT. The study primarily employs a PIE Model that encompasses three merger phases, i.e. pre-merger planning (P), merger integration (I) and post-merger evaluation (E). As such, the study aims to shed light on the critical success factors in these three merger phases that will contribute to the overall success of the merger between the two companies. Corporate mergers represent part of a corporate business strategy used by many firms to achieve various objectives. For example, mergers can be used to penetrate into new markets and new geographic regions, gain technical and or management expertise and knowledge, or allocate capital. In order to survive and grow, business organisations often utilise mergers and acquisitions strategically. Nonetheless, many corporations worldwide utilise mergers as one of the most frequently selected instruments for growth. Understanding the sources and or determinants of value creation or value loss is vital to comprehending the causes of success and failure of corporate mergers. However repeated analyses by researchers, academicians, business gurus, management consultants and investment bankers have all reached the same conclusion: in the medium term, fewer than half of all mergers add value. The shareholders whose company is bought end up richer; the shareholders of the buyer seldom do. There is plenty of scope for failure. Indeed, the marvel is that any mergers create value at all. Initially, many destroy it. Mergers suddenly throw together two teams of managers who have inevitably spent their working lives competing with each other prior to the merger. Mergers also scare employees, who know that 'economies of scale' spell redundancy. They signal to competitors that customers, suppliers and good staff are up for grabs. They wreck carefully nurtured corporate cultures. Historically, mergers and acquisitions have consistently been considered the domain of economists and market strategists rather than the behavioral sciences. Within the terms of the rational economic model, the activity is conceptualized as exclusively an association of financial and strategic convenience, which will lead to rapid and substantially increased profitability. Financial analysts frequently fail to recognize that the merger or acquisition is an important human as well as financial activity.From the study conducted and from the findings obtained, it is made to understand that influencing the success of Corporate Merger in Malaysia. Other than that, the outcome from the study is both purpose or objective as well as obtaining of reliable and valid information about the target were the most significant dimension in the pre-merger planning and both are equally important. The most important critical success factor in the merger integration process was the establishment of a sense of unity between the two merging firms. In addition, the identification of effective merger integration practices as soon as the merger deal is confirmed was the most crucial dimension in the merger integration phase. Market share gains or losses was also identified as the highest-ranking factors in the post-merger evaluation process. To add, Value-Based Management (VBM) proved to have significant and popularity in evaluating performance gains in the corporate merger. Towards the case study, the significance of the study is to understand corporate restructuring and the factors that influence the success as well as the corporate exercises.